Helping doctoral students teach: transitioning to early career academia through cognitive apprenticeship. Issue 4 (3rd July 2016) - Greer, Dominique A.; Cathcart, Abby; Neale, Larry
ABSTRACT: Doctoral training is strongly focused on honing research skills at the expense of developing teaching competency. As a result, emerging academics are unprepared for the pedagogical requirements of their early-career academic roles. Employing an action research approach, this study investigates the effectiveness of a competency-based teaching development intervention that aims to improve the teaching self-efficacy of doctoral candidates. To conduct this research, we apply the theoretical framework of Cognitive Apprenticeship Theory, a theory of social learning that requires learners to participate in a community of inquiry. Participants report significantly higher levels of teaching self-efficacy and a stronger sense of connectedness to the wider academic community.